Game-Based Interactive Multimedia as a Learning Media for Indonesian Language to Improve Students’ Literacy - Ni Putu Reisya Utari Putri; I Komang Sudarma; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2025)
The low literacy skills of early-grade students and the limited use of innovative and engaging media in learning have become a major challenge in developing reading and writing abilities. This study aims to analyze and test the effectiveness of game-based interactive multimedia as an Indonesian language learning medium to enhance students’ literacy skills. The research employs a developmental research design using the ADDIE model and adopts a one-group pretest-posttest design. The subjects consisted of nine second-grade students in a small-group trial and 29 first-grade students in a field trial. Data were collected through expert validation questionnaires, reading and writing performance tests, interviews, and observations, using instruments that had been tested for validity and reliability. Data analysis was conducted through descriptive quantitative and qualitative methods, supported by inferential statistical analysis (t-test) to examine the effectiveness of the developed product. The findings reveal a significant improvement in students’ reading and writing skills after using the game-based interactive multimedia. The developed media is thus declared effective and feasible for improving early literacy in Indonesian language learning. The study implies that teachers need training and pedagogical support to integrate game-based interactive multimedia optimally, and schools should provide adequate technological infrastructure to sustain its implementation. Furthermore, the research encourages the development of similar multimedia innovations across various subjects and educational levels to improve overall learning quality.